ACSM's resources for the exercise physiologist a practical guide for the health fitness professional - Magyari, Peter; Lite, Randi; Kilpatrick, Marcus; Schoffstall, James (Wolters Kluwer Health, 2018)
"Provide the most current, competent guidance to your clients and success on the exam with this official preparation book for the ACSM Certified Exercise Physiologist examination. Reflecting key changes of the Tenth Edition of ACSM's Guidelines for Exercise Testing and Prescription, this Second Edition includes the new per-participation guidelines, incorporates ACSM's Exercise is Medicine global health initiative throughout, and offers up-to-date coverage of the full scope of ACSM EP-C practice domains, including the information you need to provide effective program options for both healthy and special populations." -- Back cover